Keys to Successfully Choosing Enterprises That Suit Your Small Farm - Robert Hochmuth; Larry Halsey; George Hochmuth; Chad Hutchinson; Linda Landrum (EDIS, 2008)
HS-1121, an 11-page fact sheet by Robert Hochmuth, Larry Halsey, George Hochmuth, Chad Hutchinson, and Linda Landrum, helps farmers begin the decision-making process of evaluating alternative enterprises. It discusses key points to consider, and how to take a resource inventory before getting started. Published by the UF Department of Horticultural Sciences, September 2007.